(untitled) (Latakia University Journal -Engineering Sciences Series, 2018)
A numerical simulation of plate loading test using finite element method (FEM) and Plaxis 2D in order to investigate the effective parameters on the modulus of subgrade reaction .Some real plate loading test are numerically modeled and calibrated using two types of material models: mohr-coulomb MC and hardening soil HS.The obtained results from MC are better than those obtained from HS, so material model MC is adopted to generate plate load settlement curves, for a group of soil classified by DIN –Code.The results shows that for the same soil parameters the modulus of subgrade reaction is decreased as the side dimension of plate is increased and as the plasticity of soil is increased then the modulus of subgrade reaction is decreased . Depending on the obtained results a relationship is suggested to calculate the modulus of subgrade reaction in cohesive soil. Then a comparison is made between the suggested relation and (Selvadurai, Meyerhof & baike, Klopple & Glock) relations ,which shows a good coincidence. يتناول هذا البحث دراسة لأهم البارامترات المؤثرة على قيمة معامل الاستناد المرن ،وذلك من خلال النمذجة العددية لتجارب صفائح التحميل باستخدام طريقة العناصر المنتهية (FEM) وبرنامج (Plaxis 2D)،حيث تمت نمذجة بعض التجارب الحقلية الحقيقية وتبين نتيجة معايرة النماذج على تجارب حقيقية أن موديل موركولومب MC يعبر عن السلوك الإجهادي-التشوهي للتربة بشكل أفضل من موديل تصلب التربة HS ،حيث تتقارب منحنيات التحميل الحاسوبية الناتجة بشكل أفضل مع المنحني الحقيقي وبناء عليه تم اعتماد موديل موركولومب في توليد النماذج الحاسوبية المدروسة من أجل مجموعة من الترب المتماسكة المصنفة حسب الكود الألماني وفقاً لدليل السيولة. أظهرت المنحنيات التي درست تغير معامل الاستناد المرن أنه ومن أجل نفس التربة فإن قيمة معامل الاستناد المرن تقل بازدياد قطر الصفيحة ،كما أنه بازدياد لدونة التربة تقل قيمة هذا المعامل. بناء على النتائج تم اقتراح علاقة رياضية لحساب معامل الاستناد المرن لحالة الترب المتماسكةC,Φ) ) ،أعطت هذه العلاقة توافقاً مقبولاً مع الأبحاث السابقة في هذا المجال.